Levels of students’ understanding on infinity - Hannula, Markku S.; Pehkonen, Erkki; Maijala, Hanna; Soro, Riitta (Teaching Mathematics and Computer Science, 2006)
Here we report some results of a two-year study for grades 5-6 and 7-8 (during the academic years 2001-03). The study included a quantitative survey for approximately 150 Finnish mathematics classes out of which 10 classes were selected to a longitudinal part of the study. Additionally, 40 students from these classes participated also a qualitative study. This paper will focus on students’ understanding of infinity and the development of that understanding. The results show that most of the students did not have a proper view of infinity but that the share of able students grew, as the students got older.